KENDALA PENGGUNAAN IT SEBAGAI MEDIA BELAJAR DI SMP NEGERI 4 GELUMBANG - Rahma Dalena; Sri Maryani; Dencik Dencik; Dwi Amelia Galuh Primasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is a qualitative descriptive study that aims to provide an explanation of the constraints of using technology as a medium of learning in Gelumbang 4 Middle School. The informants in this study included teachers of Gelumbang 4 Middle School, headmaster or vice principal and several students through observation techniques, and interviews. The results of this study indicate that the constraints in the use of learning media technology in Gelumbang Public Middle School are as follows: (1) the lack of media available in school; (2) teacher limitations in using technology as a learning medium; (3) unavailability of time for making learning media; and (4) There are some teachers who do not understand the function of media learning.